Influence of oestrogen on satellite cells and myonuclear domain size in skeletal muscles following resistance exercise. Issue 5 (11th July 2022) - Hung, Yung‐Li; Sato, Ayami; Takino, Yuka; Ishigami, Akihito; Machida, Shuichi
Abstract: Background: Oestrogen deficiency reduces skeletal muscle mass and force generation in postmenopausal women. Muscle mass is maintained by satellite cells, which are regulated by oestrogen. Although oestrogen therapy enhances muscle hypertrophy induced by resistance training in postmenopausal women, the molecular mechanism is unclear. Methods: Adult female rats (10 weeks old) were divided into six groups: sham sedentary (Sham‐Sed), sham climbing training (Sham‐CT), ovariectomy sedentary (OVX‐Sed), ovariectomy climbing training (OVX‐CT), ovariectomy plus oestrogen treatment sedentary (OVX+E‐Sed), and ovariectomy plus oestrogen treatment climbing training (OVX+E‐CT). At 8 weeks after ovariectomy, rats in the training group were trained (one session every 3 days for 8 weeks) to climb a ladder while bearing a load. Oestrogen treatment involved subcutaneous insertion of a 17β‐oestradiol pellet. After 8 weeks, the flexor hallucis longus muscle was collected and analysed. Results: Following climbing training, the flexor hallucis longus muscle mass and muscle‐to‐body weight ratios were dramatically increased by training (main effect of training, P  < 0.01); the OVX+E‐CT group showed the highest values (main effect of group, P  < 0.01). The cross‐sectional area of all muscle fibre types was increased by training (main effect of training, P  < 0.01). Particularly, the cross‐sectional area of MHC IIa in the OVX+E‐CT group was significantly larger than that in the Sham‐CT and OVX‐CT groups. Satellite cell numbers were increased in all training groups (main effect of training, P  < 0.05), and the myonuclear number was increased by training (main effect of training, P  < 0.01), but there was no main group effect. The myonuclear domain size of all muscle fibre types and MHC IIa was increased in all training groups (main effect of training, P  < 0.01) and showed a main group effect ( P  < 0.01). The myonuclear domain sizes of all muscle fibre types and MHC IIa in the OVX+E‐CT group were significantly larger than those in the Sham‐CT and OVX‐CT groups. The total RNA contents revealed main effects of training and the group ( P  < 0.01); the OVX+E‐CT group showed the highest contents (main effect of group, P  < 0.01). The mRNA and protein levels of rpS6 were increased in the OVX+E‐Sed and CT groups (main effects of group, P  < 0.05). Particularly, the 28S ribosomal RNA content in OVX+E‐Sed group was significantly higher than that in the OVX‐Sed group. Conclusions: Oestrogen enhanced the resistance training‐induced increase in myonuclear domain size but did not affect satellite cells and ribosome biogenesis.